Antimicrobial Study of Clinical Mastitic Milk Samples of Cows in and Around Bikaner - Morwal, Sandhya; Singh, AP; Sharma, SK; Goklaney, Deepika (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Mastitis, an inflammatory condition of the mammary gland, is one of the most economically important diseases of dairy herds. This disease is more prevalent in high yielding dairy cattle. It is caused due to colonization of pathogenic bacteria causing series of events that lead to major alteration in the mammary tissues and composition of milk secreted from the tissue cells (Batavani et al., 2007; Goel et al., 2008). Clinical mastitis is recognized by abnormal milk, varying degree of mammary gland inflammation (redness, heat, swelling and pain) with or without illness of the cow. Mastitis in dairy animals leads to heavy economic losses due to reduction in milk production, altered composition, and cost of treatment of affected animals. The clinical mastitis in different cases can be identified by external symptoms such as udder swelling, touch, pain, redness and hardness of the udder. The objective of the present study was to assess the sensitivity of bacterial isolates from mastitic milk samples of cows to some selected antibiotics.